Cherry Picking Patients: Examining the Interval Between Patient Rooming and Resident Self‐assignment. (13th February 2016) - Patterson, Brian W.; Batt, Robert J.; Wilbanks, Morgan D.; Otles, Erkin; Westergaard, Mary C.; Shah, Manish N.
Abstract: Objective: We aimed to evaluate the association between patient chief complaint and the time interval between patient rooming and resident physician self‐assignment ("pickup time"). We hypothesized that significant variation in pickup time would exist based on chief complaint, thereby uncovering resident preferences in patient presentations. Methods: A retrospective medical record review was performed on consecutive patients at a single, academic, university‐based emergency department with over 50, 000 visits per year. All patients who presented from August 1, 2012, to July 31, 2013, and were initially seen by a resident were included in the analysis. Patients were excluded if not seen primarily by a resident or if registered with a chief complaint associated with trauma team activation. Data were abstracted from the electronic health record (EHR). The outcome measured was "pickup time, " defined as the time interval between room assignment and resident self‐assignment. We examined all complaints with >100 visits, with the remaining complaints included in the model in an "other" category. A proportional hazards model was created to control for the following prespecified demographic and clinical factors: age, race, sex, arrival mode, admission vital signs, Emergency Severity Index code, waiting room time before rooming, and waiting room census at time of rooming. Results: Of the 30, 382 patients eligible for the study, the median time to pickup was 6 minutes (interquartile range = 2–15 minutes). After controlling for the above factors, we found systematic and significant variation in the pickup time by chief complaint, with the longest times for patients with complaints of abdominal problems, numbness/tingling, and vaginal bleeding and shortest times for patients with ankle injury, allergic reaction, and wrist injury. Conclusions: A consistent variation in resident pickup time exists for common chief complaints. We suspect that this reflects residents preferentially choosing patients with simpler workups and less perceived diagnostic ambiguity. This work introduces pickup time as a metric that may be useful in the future to uncover and address potential physician bias. Further work is necessary to establish whether practice patterns in this study are carried beyond residency and persist among attendings in the community and how these patterns are shaped by the information presented via the EHR.